2015
DOI: 10.1002/ange.201508715
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical β‐Mo2C Nanotubes Organized by Ultrathin Nanosheets as a Highly Efficient Electrocatalyst for Hydrogen Production

Abstract: Production of hydrogen by electrochemical water splitting has been hindered by the high cost of precious metal catalysts,s uch as Pt, for the hydrogen evolution reaction (HER). In this work, novel hierarchical b-Mo 2 Cn anotubes constructed from porous nanosheets have been fabricated and investigated as ahigh-performance and low-cost electrocatalyst for HER. An unusual template-engaged strategy has been utilized to controllably synthesize Mo-polydopamine nanotubes,w hich are further converted into hierarchical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(109 citation statements)
references
References 45 publications
3
106
0
Order By: Relevance
“…Combined with the polarization curves analyzed above, we may safely draw the conclusion that the 3D porous structure not only contributes to the charge transfer but can also produce an enlarged active area and thus contribute favorably to the final hydrogen evolution. These results also reveal that MoCN-3D is among the most active nonprecious HER electrocatalysts in acidic solutions [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][32][33][34][35][36][37][38] (Supplementary Tables S3 and S4). …”
Section: Catalytic Performancementioning
confidence: 68%
See 1 more Smart Citation
“…Combined with the polarization curves analyzed above, we may safely draw the conclusion that the 3D porous structure not only contributes to the charge transfer but can also produce an enlarged active area and thus contribute favorably to the final hydrogen evolution. These results also reveal that MoCN-3D is among the most active nonprecious HER electrocatalysts in acidic solutions [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][32][33][34][35][36][37][38] (Supplementary Tables S3 and S4). …”
Section: Catalytic Performancementioning
confidence: 68%
“…[5][6][7][8][9][10][11] Particularly, β-phase molybdenum carbides have been demonstrated as highly active HER catalysts, even though they are bulky particles, and their performances could be further improved by constructing proper nanostructures. [12][13][14][15][16][17] It was revealed that nanorods of β-Mo 2 C work better as an electrocatalyst for HER than bulk β-Mo 2 C. 12 In addition to the morphology contribution, hybridization with heteroatom-doped graphitic carbon could further improve its performance because the effective coupling between β-Mo 2 C and N-doped graphitic carbon can greatly modify the work function of the hybrid and thus reduce the proton adsorption and the reaction barrier. 16 Other than tailoring the nanostructure and chemical composition of the catalysts, the HER behavior can also be optimized through the manipulation of the whole architecture of the electrocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The high intensity ratio of theseb ands (I D /I G = 1.01) indicates that the carbon matrix in RuP x @NPC is rather disordered with significant structuraldefects. [44,45] The morphologies of the samples were further characterized by using SEM and SEM mapping. The SEM image presentedi n Figure 3a showst he well-defined nanospherical morphology of the Ru-P polymer precursor.T he clearm orphology of Ru-P polymer nanospheres with ap article size of approximately 100 nm is shown in Figure3b.…”
Section: Resultsmentioning
confidence: 99%
“…[43] Lou et al have further synthesized the well-designed porous MoC x nano-octahedrons [183] and the hierarchical β-Mo 2 C nanotubes [184] by thermal conversion of molybdenum-based metal-organic frameworks (MOFs) and MoO 3 -templated Mo-polydopamine nanorods, respectively, as shown in Figure 14a. The synthesis of MoC x nano-octahedrons relies on the confined and in situ carburization reaction occurring in a unique MOFs-based compound (NENU-5), consisting of a Cu-based MOFs (HKUST-1) host and Mo-based Keggin polyoxometalates (POMs) guest resided in pores, which enables the uniform formation of ultrafine MoC nanocrytallites embedded in an amorphous carbon matrix without any coalescence and excess growth (Figure 14b).…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Figure 14c,d give the synthetic route and TEM image of the hierarchical β-Mo 2 C nanotubes, accordingly. [184] Mo-polydopamine hybrid nanotubes constructed by 2D ultrathin nanosheets are then synthesized by in situ polymerization of Mo-dopamine complex using MoO 3 nanorods as the self-degradable template and Mo source. The hierarchical β-Mo 2 C nanotubes would be next obtained by directly carburizing the Mo-polydopamine nanotubes under an inert atmosphere.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%